PENGARUH MODAL INTELEKTUAL DAN KEUNGGULAN BERSAING TERHADAP KINERJA KEUANGAN - Purwanto Purwanto; Nanda Fito Mela (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study aims to find empirical evidence of the effect of intellectual capital and competitive advantage on financial performance in manufacturing companies listed on the Indonesian stock exchange in 2016-2018. By using the Public - Value Added Intellectual Coefficients (VAICTM) model, this study examines the relationship between the value-added efficiency (VAICTM) of the company's three main resources in the form of (capital used efficiency (CEE), human capital efficiency (HCE) and structure capital efficiency (SCE). )) competitive advantage to the company's financial performance as proxied through Return on Assets (ROA) and Return on Equity (ROE). Data were drawn from 72 manufacturing companies listed on the IDX in 2016-2018. The results show that Capital Employed Efficiency (CEE) affects the financial performance of ROA and ROE proxies, Human Capital Efficiency (HCE) does not affect the proxy performance of ROA but affects the proxy performance of ROE, Structural Capital Efficiency (SCE) affects the financial performance of ROA proxies. and ROE, the Value-added Intellectual Coefficient (VAICTM) does not affect the financial performance of ROA proxies, but it does affect the financial performance of ROE proxies, and Competitive Advantage (CA) has no effect on the financial performance of ROA and ROE proxies.